The role of OTAs in Bali's tourism landscape: Maximizing hotel bookings - Sumawidari, Ida Ayu Ketut; Damayanti, Ida Ayu Kade Werdika; Nadra, Nyoman Mastiani; Solihin, Solihin (YAYASAN MITRA PERSADA NUSANTARA, 2025)
This study explores the pivotal role of Online Travel Agencies (OTAs) in maximising villa bookings within Bali's dynamic tourism landscape. The primary objective is to analyse how OTAs influence booking patterns, enhance visibility, and contribute to revenue generation for villa owners. Data collection involved a mixed-method approach, combining quantitative surveys distributed to villa owners and qualitative interviews with industry stakeholders. The analysis employed statistical techniques to identify trends in booking behaviour and thematic analysis to interpret qualitative insights. Findings indicate that OTAs significantly increase the reach of villa listings, facilitating access to a global audience. Additionally, the study reveals that strategic partnerships with OTAs can lead to improved occupancy rates and higher revenue per booking. However, challenges such as commission fees and market saturation are noted, necessitating a balanced approach to OTA utilisation. The conclusion underscores the importance of integrating OTA strategies with direct marketing efforts to optimise bookings while maintaining brand identity. This research contributes to the existing literature on tourism management and provides actionable insights for villa owners seeking to enhance their competitive edge in Bali's tourism market.